Layanan referensi di pusat perpustakaan UIN Syarif Hidayatullah Jakarta - Maryulisman Maryulisman (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2016)
This paper discusses about Reference Service at Central Library of State Islamic University,The objective of this article is to describe the practices of reference services and the barriers indelivering the services. Based on the study it was found that the reference service doesn’t functionproperly either in the type of the service or the service system provided. The service system isoffered manually. Moreover, the competencies of reference librarians are still unsufficcient,particularly the competency of Arabic proficiency. It can hinder considerably in deliveringreference services effectively.